2010
DOI: 10.1021/es903524m
|View full text |Cite
|
Sign up to set email alerts
|

Hands, Water, and Health: Fecal Contamination in Tanzanian Communities with Improved, Non-Networked Water Supplies

Abstract: Almost half of the world's population relies on non-networked water supply services, which necessitates in-home water storage. It has been suggested that dirty hands play a role in microbial contamination of drinking water during collection, transport, and storage. However, little work has been done to evaluate quantitatively the association between hand contamination and stored water quality within households. This study measured levels of E. coli, fecal streptococci, and occurrence of the general Bacteroidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
170
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(189 citation statements)
references
References 21 publications
16
170
1
Order By: Relevance
“…The recontamination of water between source and household is well documented in the literature for many parts of the world (Wright et al , 2004) and the sources of recontamination are similar to those found in previous studies in Honduras (Trevett et al , 2005) and Tanzania (Pickering et al , 2010b). Finally, the water and sanitation behaviors and practices of the residents have likewise been observed in a number of previous studies (Thompson, 2001;.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The recontamination of water between source and household is well documented in the literature for many parts of the world (Wright et al , 2004) and the sources of recontamination are similar to those found in previous studies in Honduras (Trevett et al , 2005) and Tanzania (Pickering et al , 2010b). Finally, the water and sanitation behaviors and practices of the residents have likewise been observed in a number of previous studies (Thompson, 2001;.…”
Section: Discussionsupporting
confidence: 81%
“…Although this method is adequate for rinsing o↵ dirt, it is ine↵ective at removing bacteria. As was found in previous studies, improper hand-hygiene might therefore be a significant source of coliforms in the community (Pickering et al , 2010b) which might lead to diarrhea (Aiello et al , 2008). The percentage of positive results are higher than has been found previously by Trevett et al (2005) who found a lower percentage 44% (n = 14) of contaminated hands than was found in this study, 96% (n = 48).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…[2][3][4] High concentrations of fecal indicator bacteria (FIB) and pathogens can be in food, water, soil, and on hands and surfaces. 3,5 Elevated levels of fecal contamination in the environment are attributed to inadequate sanitation, a leading cause of child morbidity and mortality from diarrheal diseases, malnutrition, and stunting. 6 In addition, fecal contamination on surfaces is linked to increased risk of diarrheal disease, as highlighted by a study at a child care center in the United States.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] By acquiring pathogens from surfaces in the environment and transferring them to the mouth or nose, hands constitute a key route for the transmission of infectious diseases. 6 Handwashing with soap has been shown to decontaminate hands [7][8][9] and reduce the risk of ingesting pathogens and acquiring diarrhea.…”
Section: Introductionmentioning
confidence: 99%